Compensation of Dynamic Phase Error in the Formation of Orthogonal Components of Input Signals in Microprocessor Protections - F. A. Romaniuk; Yu. V. Rumiantsev; V. Yu. Rumiantsev; I. V. Novash (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2022)
In microprocessor protections of electric power systems, the controlled information parameters of input signals are determined using their orthogonal components. To form these components, digital Fourier filters which have inertia are most widely used. As a result, transient modes of orthogonal components formation are accompanied by the appearance of a dynamic error. It consists of dynamic amplitude and phase errors, which can significantly affect the functioning of the corresponding measuring elements and cause the possibility of their excessive triggering during external short circuits and slowing down the triggering during internal short circuits. The reduction of the influence of these factors on the behavior of measuring elements is ensured by the use of high-speed shapers to isolate orthogonal components, as well as by compensating for dynamic phase error. The proposed method of forming orthogonal components of a signal with compensation for dynamic phase error is based on obtaining orthogonal Fourier components, followed by determining from their samples the calculated components that coincide or are shifted in phase relative to the orthogonal Fourier components, respectively, in steady-state and transient modes. The resulting orthogonal components with minimal dynamic phase errors are calculated in accordance with samples of calculated orthogonal components and Fourier components. The efficiency of the proposed solution was evaluated by a computational experiment using a digital model implemented in the MATLAB-Simulink dynamic modeling environment. At the same time, both sinusoidal input signals and complex ones with an aperiodic component and higher harmonics were used as test actions. As a result of the studies carried out, it has been found that the proposed method of compensation for dynamic phase error in the formation of orthogonal components is workable and effective for both sinusoidal and complex input signals. The developed compensation method reduces the dynamic phase error of digital Fourier filters by three to four times.